La « femme·eux·ze » musique québécoise - Blais-Tremblay, Vanessa (2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.
Keywords: 2000 à aujourd'hui; DIG; amériques; approches et analyses; bibliographie; discipline; discours dominant; genre; identités LGBTQIA2+; musique; outils; ouvrages de références; périodes historiques; québec; régions géographiques; sexualité; systèmes d'oppressions; thématiques

AfroTrans : perspectives, entretiens, poésie, fiction - Danjé, Michaëla; Cxsper, Blxck; Brisac, Michaël; Bémé, Hélène; Descieux, Kellysha; Fénwar, Véli; Gabriel, Joao; Kounkou, Sofiane-Akim; Kuchenga; Lari, Sika; Louïz; Mon-Ink, D.; et al. (Cases Rebelles Editions, 2021)
« Au croisement étoilé de la négritude et de la transidentité, l’accidentelle et lumineuse poésie de nos vies lancée au monde. » Dans cet ouvrage collectif, la parole est donnée exclusivement à des personnes trans noires, vivant en France pour la grande majorité. Ce recueil coordonné par Michaëla Danjé, femme trans membre et co-fondatrice de Cases Rebelles, contient des essais, de la fiction, de la poésie, des interviews, etc. Ce livre est constitué d’une multiplicité de voix, de perspectives et d’expériences diverses. Différentes générations sont également représentées. AfroTrans est beau, complexe, riche de lumière, d’amour et de force !
Keywords: anthologie; approches et analyses; corps; cours; discours dominant; fem3100; identités LGBTQIA2+; outils; ouvrages de références; personnes trans*; premier cycle; racisme; sexisme; systèmes d'oppressions; thématiques; violences

Feu!: abécédaire des féminismes présents - Dorlin, Elsa (Libertalia, 2021)
Plutôt que de réduire le féminisme à des revendications faites à l’État, au patron, au chef ou à papa, pour plus de lois, plus de “sécurité”, à n’être que le porte-drapeau ou le cache-misère du capitalisme, de tel ou tel gouvernement nationaliste, ces histoires des féminismes présents rappellent et font résonner ensemble nos vies féministes. Ce livre fonctionne comme un abécédaire, un manuel, une boîte à outils, un dictionnaire amoureux, dans lequel échanger des idées, affûter des armes, écouter des voix, partager des expériences et des pratiques, vibrer pour des luttes présentes. Il s’adresse à tous·tes : il contient à la fois des ressources et foisonne de références utiles, de notions, mais il est fabriqué par des plumes et des voix, des points de vue situés sur des retours d’expériences collectives, des itinéraires politiques et intimes, des réflexions et des rétrospections sur des parcours, des engagements, des révoltes et des espoirs. En pluralisant les styles, en se situant à la fois du côté de la théorie et de la pratique, de la création, des écritures au “nous” et au “je”, il témoigne de la force d’une approche féministe de l’histoire intellectuelle et politique. Il est dédié à toutes les résistantes anonymes au quotidien des violences les plus crasses, à celles qui embrasent les tribunaux, cassent des genoux et brisent les vitrines, à celles qui inventent mille tactiques imperceptibles pour survivre et se mettre à l’abri, à la mémoire de celles dont les noms recouvrent les murs de nos villes la nuit, à la puissance des collectifs qui se font, à ceux qui se sont défaits, qui se sont (re)constitués ailleurs ou autrement, à ce qui nous lie.
L'article "Justice reproductive" de Bessaïh, Nesrine, 2021 a été donné en lecture au cours SEX2283. L'entrée "Cisgenre" d'Alexandre Baril a été donné en lcture au cours SOC2014.
Keywords: afro-féminisme; approches et analyses; corps; cours; droits des femmes*; fem3100; féminisme décolonial; féminismes noirs; genre; identités LGBTQIA2+; intersectionnalité; inégalités; outils; ouvrages de références; premier cycle; queer; racisme; sex2283; sexisme; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; écoféminisme

The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Intersectionality in feminist and queer movements: Confronting privileges - Evans, Elizabeth (Routledge, 2020)
Examining the ways in which feminist and queer activists confront privilege through the use of intersectionality, this edited collection presents empirical case studies from around the world to consider how intersectionality has been taken up (or indeed contested) by activists in order to expose and resist privilege. The volume sets out three key ways in which intersectionality operates within feminist and queer movements: it is used as a collective identity, as a strategy for forming coalitions, and as a repertoire for inclusivity. The case studies presented in this book then evaluate the extent to which some, or all, of these types of intersectional activism are used to confront manifestations of privilege. Drawing upon a wide range of cases from across time and space, this volume explores the difficulties with which activists often grapple when it comes to translating the desire for intersectionality into a praxis which confronts privilege. Addressing inter-related and politically relevant questions concerning how we apply and theorise intersectionality in our studies of feminist and queer movements, this timely edited collection will be of interest to students and scholars from across the social sciences and humanities with an interest in gender and feminism, LGBT+ and queer studies, and social movement studies.
Keywords: LGBTQIA2+; approches et analyses; identités LGBTQIA2+; intersectionnalité; militance; outils; ouvrages de références; privilèges; queer; ressource en ligne; systèmes d'oppressions; thématiques

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

The Black studies reader - Bobo, Jacqueline; Hudley, Cynthia; Michel, Claudine (Routledge, 2004)
Black studies emerged from the tumultuous social and civil rights movements of the 1960s and empowered African Americans to look at themselves in new ways and pass on a dignified version of Black history. However, it also enriched traditional disciplines in profound and significant ways. Proponents of Black and ethnic studies confronted the false notion that scholarly investigations were objective and unbiased explorations of the range of human knowledge, history, creativity, artistry, and scientific discovery. As they protested against hegemonic notions like universal psychology and re-evaluated canonical texts in literature, a new model of academic inquiry evolved: one committed to serving a range of populations, that critiqued traditional politics, culture, and social affairs, and worked with activist energy for the transformation of the existing social order. With an all-star cast of contributors, The Black Studies Reader takes on the history and future of this multi-faceted academic field. Topics include Black feminism, cultural politics, Black activism, lesbian and gay issues, African American literature and film, education, and religion. This authoritative collection takes a critical look at the current state of Black studies and speculates on where it may go from here.
Keywords: LGBTQIA2+; afro-féminisme; amériques; approches et analyses; féminisme islamique; histoire et politique; identités LGBTQIA2+; militance; outils; ouvrages de références; racisme; ressource en ligne; régions géographiques; sexualité; système colonial; systèmes d'oppressions; thématiques; états-unis

Dykewords: An anthology of lesbian writings - Lesbian Writing and Publishing Collective. (Women's Press, 1990)
An entertaining and refreshing anthology that includes writing about the vibration of lesbian love, cultural identity, sexual fantasy, overcoming alcohol abuse, a teenage coming out, lesbian history, imaginative lesbian antics for lesbian survival and much, much more
https://www.deslibris.ca/ID/412587
Keywords: anthologie; approches et analyses; corps; histoire et politique; identités LGBTQIA2+; littérature; outils; ouvrages de références; personnes lesbiennes; poésie; racisme; ressource en ligne; roman; santé; sexisme; sexualité; système colonial; systèmes d'oppressions; thématiques